"Connecting patients and therapists remotely using technology is feasible and facilitates exercise adherence after stroke". Issue 2 (17th February 2020) - Simpson, Dawn B.; Bird, Marie-Louise; English, Coralie; Gall, Seana L; Breslin, Monique; Smith, Stuart; Schmidt, Matthew; Callisaya, Michele L.
ABSTRACT: Purpose : Repetitive task practice after stroke is important to improve function, yet adherence to exercise is low. The aim of this study was to determine whether using the internet, a tablet application, and a chair sensor that connected to a therapist was feasible in monitoring adherence and progressing a functional exercise at home. Methods : Ten participants with stroke completed a 4-week sit-to-stand exercise using the technology at home (ACTRN12616000051448). A therapist remotely monitored exercise adherence, progressed goals, and provided feedback via the app. Measures of feasibility (design, recruitment/withdrawals, adherence, safety, participant satisfaction and estimates of effect on function) were collected. Results : Participants' mean age was 73.6 years [SD 9.9 years]. The system was feasible to deliver and monitor exercise remotely. All participants completed the study performing a mean 125% of prescribed sessions and 104% of prescribed repetitions. Participants rated the system usability (78%), enjoyment (70%) and system benefit (80%) as high. No adverse events were reported. The mean pre- and post-intervention difference in the total short performance physical battery score was 1.4 (95% CI 0.79, 2.00). Conclusions : It was feasible and safe to prescribe and monitor exercises using an app and sensor-based system. A definitive trial will determine whether such technology could facilitate greater exercise participation after stroke.